2012
DOI: 10.1177/0042085912446165
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Process Drama on Elementary Students’ Written Language

Abstract: This article describes the influence of process drama on fourth grade students' written language productivity and specificity. Participants included 16 students with learning and/or behavioral challenges at an urban public charter school. The influence of process drama on students' written language was compared across contextualized and decontextualized activities to identify associations between activities and language outcomes. Significant increases in students' written language productivity and specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Arts integration is an approach to academic instruction that links an arts area with a content area to reach a deeper level of engagement, learning, and reflection (Anderson, 2012; Loughlin & Anderson, 2015). In arts-integration classrooms, students are working “with” and “through” art forms to reach academic, social, and personal goals (Cornett, 2007, p. 13).…”
Section: Teaching Academic Skills Through Arts Integrationmentioning
confidence: 99%
“…Arts integration is an approach to academic instruction that links an arts area with a content area to reach a deeper level of engagement, learning, and reflection (Anderson, 2012; Loughlin & Anderson, 2015). In arts-integration classrooms, students are working “with” and “through” art forms to reach academic, social, and personal goals (Cornett, 2007, p. 13).…”
Section: Teaching Academic Skills Through Arts Integrationmentioning
confidence: 99%
“…Arts integration benefits both hard skills, measured by tests, and soft skills, or, what is referred to as non-cognitive factors, typically associated with workforce development (Kautz, Heckman, Diris, Ter Weel, & Borghans, 2014). When elementary classroom teachers integrate the arts with non-arts subjects, students' ELA achievement improves, particularly achievement associated with literate language features (Anderson, 2012;Anderson & Loughlin, 2014), speaking and listening skills (Greenfader & Brouillette, 2013), and high stakes tests (Walker, Bosworth McFadden, Tabone, and Finklestein, 2011). In tandem, integrating the arts also points to increased mathematics achievement, specifically success related to problem solving and using mathematical symbols (An, Capraro, and Tillman 2013), improved student attitudes regarding math (Werner, 2011), and higher standardized test achievement in state high-stakes math assessments (Cunnington et al, 2014;Harloff, 2011).…”
Section: Review Of Related Literature On Arts Integrationmentioning
confidence: 99%
“…Dramatic art was introduced for the first time into the Croatian National Curriculum Framework for preschool education and general compulsory and high school education as a separate art field (NOK, 2011). Research has shown that dramatic art influences the development of a child's linguistic skills and empathy (Adomat, 2012;Anderson, 2012;Barnes, 2014;Holland, 2009), and increases the pupils' motivation for and engagement in learning (Martin et al, 2013). In the Croatian curriculum, the learning outcomes clearly show the effort to recognize drama education within school and subject curricula not only as content of particular subjects (e.g.…”
Section: The Importance Of Drama In Educationmentioning
confidence: 99%
“…Dramska umjetnost kao posebno umjetničko polje prv je put upisana u hrvatski Nacionalni okvirni kurikulum za predškolski odgoj i obrazovanje te opće obvezno i srednjoškolsko obrazovanje (NOK, 2011). Istraživanja su pokazala da dramska umjetnost utječe na razvoj djetetovih jezičnih sposobnosti i empatije (Adomat, 2012;Anderson, 2012;Barnes, 2014;Holland, 2009) te povećava učenikovu motivaciju i angažiranost za učenje (Martin i drugi, 2013). U hrvatskom kurikulu iz ishoda učenja vidljivo je nastojanje da se dramska umjetnost, unutar školskih i predmetnih kurikula, prepozna ne samo kao sadržaj pojedinih nastavnih predmeta (npr.…”
Section: Važnost Dramske Umjetnosti U Odgoju I Obrazovanjuunclassified